The concepts of ethnos, ethnichnost’ and ethnicity in Russian and Western scholarship - Teziç, Mustafa Can (The New Research of Tuva, 2016)
In this article, we analyze the main theoretical points of the Russian school of ethnology (ethnography) as compared to those advanced by English-language schools. We focus on the Russian notions of ‘ethnos’ and ‘etnichnost’’ and the Western concept of ‘ethnicity’. A comparative study of the differences between these notions can help us understand the emphasis researchers lay and the implications they suggest while studying ethnic processes and phenomena in particular regions of the world, including Tuva.A comparison of the versions for basic terms of ethnology in Russian and English-speaking scholarship reveals a difference in theoretical approach. In the Russian tradition, the notion of ‘ethnos’ acts like a window into the internal structure of the term, moving to the fore such sub-fields with their own theoretical prospects as ethnopsychology and ethnic consciousness. At the same time, the term ‘ethnicity’ implies analyzing the interaction and mutual relations between various ethnic groups and the issue of their identification.The ‘ethnicity’ in the Western tradition is based on self-identification and identification of the Other (along the lines of the ‘Us v. them’ model), and on relations within a group. Researchers emphasize the fact that the English language lacks a specific word for ‘ethnic group’. ‘Ethnicity’ can be treated according to any of the three major approaches – in a constructivist, instrumentalist or primordialist way, although recently Western scholarship witnessed the rise of a ‘hybrid’, synthesizing view which unites the primordialist and constructivist strands under the name of ‘constructive primordialism’. This trend witnesses the increased importance of ethnic and even racial identities (which are features of the primordial approach) within various social structures where intense group interaction happens.These differences between theoretical approaches are primarily important for understanding how the essence and particularities of ethnic and ethnosocial processes are interpreted by various research traditions. It is also helpful for analyzing issues typical for particular ethnic entities and ethnic features within societies.
Keywords: ethnos; etnichnost’; ethnicity; ethnic group; primordialism; instrumentalism; constructivism